Self-Care and Quality of Life Among Hemodialysis Patients in A Selected Hospital, Trichy - M, PraiselinJeneta; Sarmila, Sarmila; Suresh, Suja; S, Renuga (Journal of Neonatal Surgery, 2025)
Background of the study: Hemodialysis is a treatment option for end-stage kidney disease. These individuals experience several stressful social, psychological, and physical situations that lower their quality of life. The capacity for self-care is one element that effectively raises quality of life. Materials and methods: The study assessed self-care and Quality of life among hemodialysis patients. Data were collected using a descriptive research approach and a questionnaire that includes three parts: demographic variables, Quality of life (SF 36 QOL scale), and self-care (Romberg scale). Results:The result indicates that the quality of scale is 86.6% was satisfied and self-care is 93.3% moderate. Correlation between self care and quality of life is (p<0.001, r=0.0889). Conclusion: The study findings revealed that self-care and quality of life are positively correlated, it is advised that healthcare planners educate and strengthen these hemodialysis patients' capacity for self-care to enhance their quality of life.